Radial Growth and Biomass Production of Entomopathogenic Fungal Beauveria bassiana on Various Media PERTUMBUHAN RADIAL DAN PRODUKSI BIOMASSA CENDAWAN ENTOMOPATOGEN Beauveria bassiana PADA BERBAGAI MEDIA - Dewi Ramdhania; Achmad .; Noor Farikhah Haneda (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Three different types of solid and liquid media were used to determine radial growth and biomass production of Beauveria bassiana. Radial growth in solid media was observed for about 15 day after inoculation by measuring the fungal colony diameter every 24 hours. Maximum average growth is obtained in SDAY media (5.31 cm) followed by PDA(4.79 cm) and MEA (4.21 cm). While SDBY (0.24 g) as the liquid medium used for the biomass production after 4 weeks of incubation obtained the highest biomass followed by MEB (0.19 g) and PDB (0.18 g). The result showed that Sabouraud Dextrose with Yeast Extract is the most suitable medium for B. bassiana growth.Key words : Beauveria bassiana, media, radial growth, biomass production